Optimal positioning of optodes on the scalp for personalized functional near-infrared spectroscopy investigations - Machado, A.; Cai, Z.; Pellegrino, G.; Marcotte, O.; Vincent, T.; Lina, J-M.; Kobayashi, E.; Grova, C. (Journal of neuroscience methods, 2018)
•We proposed a procedure for personalized fNIRS investigations.•We developed a method to estimate the optimal optode positions over target brain regions.•Optodes will be attached with a clinical adhesive.•Personalized fNIRS montages allowed accurate local reconstructions along the cortex.•The procedure will allow conducting studies under realistic lifestyle conditions. Application of functional Near InfraRed Spectroscopy (fNIRS) in neurology is still limited as a good optical coupling and optimized optode coverage of specific brain regions remains challenging, notably for prolonged monitoring. We propose to evaluate a new procedure allowing accurate investigation of specific brain regions. The procedure consists in: (i) A priori maximization of spatial sensitivity of fNIRS measurements targeting specific brain regions, while reducing the number of applied optodes in order to decrease installation time and improve subject comfort. (ii) Utilization of a 3D neuronavigation device and usage of collodion to glue optodes on the scalp, ensuring good optical contact for prolonged investigations. (iii) Local reconstruction of the hemodynamic activity along the cortical surface using inverse modelling. Using realistic simulations, we demonstrated that maps derived from optimal montage acquisitions showed, after reconstruction, spatial resolution only slightly lower to that of ultra high density montages while significantly reducing the number of optodes. The optimal montages provided overall good quantitative accuracy especially at the peak of the spatially reconstructed map. We also evaluated real motor responses in two healthy subjects and obtained reproducible motor responses over different sessions. We are among the first to propose a mathematical optimization strategy, allowing high sensitivity measurements. Our results support that using personalized optimal montages should allow to conduct accurate fNIRS studies in clinical settings and realistic lifestyle conditions.